Serious complications and recurrences after pelvic organ prolapse surgery for 2309 women in the VIGI‐MESH registry. (20th September 2021) - Fritel, X; de Tayrac, R; de Keizer, J; Campagne‐Loiseau, S; Cosson, M; Ferry, P; Deffieux, X; Lucot, J‐P; Wagner, L; Debodinance, P; Saussine, C; Pizzoferrato, A‐C; et al.
Abstract : Objective: To assess the incidence of serious complications and reoperations for recurrence after surgery for pelvic organ prolapse (POP) and compare the three most common types of repair. Design: Prospective cohort study using a registry. Setting: Nineteen French surgical centres. Population: A total of 2309 women participated between 2017 and 2019. Methods: A multivariate analysis including an inverse probability of treatment weighting approach was used to obtain three comparable groups. Main outcome measures: Serious complications and subsequent reoperations for POP recurrence. Results: The median follow‐up time was 17.6 months. Surgeries were native tissue vaginal repairs ( n = 504), transvaginal mesh placements ( n = 692) and laparoscopic sacropexies with mesh ( n = 1113). Serious complications occurred among 52 women (2.3%), and reoperation for POP recurrence was required for 32 women (1.4%). At 1 year the cumulative weighted incidence of serious complications was 1.8% for native tissue vaginal repair, 3.9% for transvaginal mesh and 2.2% for sacropexy, and the rates for reoperation for recurrence of POP were 1.5, 0.7 and 1.1%, respectively. Compared with native tissue vaginal repair, the risk of serious complications was higher in the transvaginal mesh group (weighted hazard ratio, wHR 3.84, 95% CI 2.43–6.08) and the sacropexy group (wHR 2.48, 95% CI 1.45–4.23), whereas the risk of reoperation for prolapse recurrence was lower in both the transvaginal mesh (wHR 0.22, 95% CI 0.13–0.39) and sacropexy (wHR 0.29, 95% CI 0.18–0.47) groups. Conclusions: Our results suggest that native tissue vaginal repairs have the lowest risk of serious complications but the highest risk of reoperation for recurrence. These results are useful for informing women and for shared decision making. Tweetable abstract: Laparoscopic sacropexy had fewer serious complications than transvaginal mesh and fewer reoperations for recurrence than vaginal repair. Tweetable abstract: Laparoscopic sacropexy had fewer serious complications than transvaginal mesh and fewer reoperations for recurrence than vaginal repair.